Pilot Test of the Comprehensive Training Program: Designing My Future for New Students at LCI VERITAS University, Costa Rica (Costa Rican Journal of Guidance & Counseling, 2025)
Objective: To evaluate the main results of the application of the pilot test of the Comprehensive Training Program: Designing My Future, specifically the MOOC Time for Everything, to first-semester students at LCI Veritas University. Methodology: This is a mixed-method study using a sequential explanatory design. Quantitative data collected in the evaluation survey and an instrument of time management habits (post- and pre-test) were used. Qualitative data from this evaluation, course products, and information from interviews with instructors were then used in-depth. The primary source was the participating students (n=161), while the other sources were two instructors representing the courses participating in the pilot test and 483 documents. Results: There is a high pedagogical quality, and the expected time management skills increased. 76% of students were highly satisfied, especially with the learning resources, instructional design, and content. In fact, 86% of students would recommend the MOOC to another peer, and 87% of the population achieved a high frequency of time management habits at the end of the MOOC, mainly in planning. Conclusions: The results of the Time for Everything MOOC pilot are evaluated as highly positive for both student training and the efforts of faculty and the Guidance Office. Its implementation is recommended across all university programs, with actions at enhancing student motivation and placing greater emphasis on effective time management strategies.
Keywords: time allocation; student adaptation; pedagogical guidance; higher education